Canola yield, forage accumulation, and nutritive value in dual‐purpose and companion cropping. Issue 1 (2nd December 2020) - Holman, Johnathon; Assefa, Yared; Stamm, Michael; Obour, Augustine K.
Abstract: Winter canola ( Brassica napus L.) production has increased in the Great Plains as producers seek a rotational and alternative crop to winter wheat ( Triticum aestivum L). However, limited information is available if canola could be used for dual‐purpose without significantly affecting grain yield. The objectives of this study were to (a) investigate dual‐purpose potential and (b) impact of companion crops on growth, survival, biomass, and grain yield of canola. The study was conducted in 2011 and 2012 at Garden City, KS. The experimental design of the study was a randomized complete block design with split‐plot arrangement. Main plot treatments were a factorial of canola cultivars (Griffin or Wichita) and companion crop treatments (none, spring triticale [ × Triticosecale Wittm. ex A. Camus], winter triticale, radish [ Raphanus raphanistrum subsp. sativus (L.) Domin], and turnip [ Brassica rapa var. rapa L.]), and the split‐plot treatments were single‐purpose (grain only) or dual‐purpose (grain and forage) management. Averaged across cultivars and years, grain yield was 70% greater when canola was used for single‐purpose (grain‐only) compared with dual‐purpose. Griffin grain yield tended to be relatively greater than Wichita in dual‐purpose use. Averaged across the two years, turnip as a companion crop decreased canola yield by 38% but resulted in greater forage accumulation. In conclusion, dual‐purpose canola has a grain yield penalty, but effects may vary by cultivar. Companion cropping did not benefit canola and in some cases negatively affected grain yield. When grain production is the primary objective, both companion cropping and forage use should be avoided.